Effect Of pH On Tungsten Removal From Chemical Mechanical Polishing (CMP) Slurry Using Dowex Marathon C Resin Of Ion Exchange - Ahmad, Nur Husni (Universiti Sains Malaysia, 2018)
The chemical mechanical polishing slurry is widely used in the semiconductor industry as a polishing agent to polish the surface of wafer. The polishing process involve the chemical and mechanical action to remove the modified layer on the surface of the wafer by tungsten slurry. The recovery of the tungsten slurry is important to help reducing the cost of operation and reduce the production of wastewater by the industry. The recovery of spent tungsten slurry is study by using the ion exchange process by using the cation resin. Cation resin used is classified as strong acid cation exchange which is the Dowex Marathon C resin. The parameter that consider in this study is the pH different of the spent tungsten slurry. The study on the characterization of the tungsten slurry is vital to understand the best recovery method for the tungsten slurry. The study of characterization of tungsten slurry involve the pH, metal content, conductivity, zeta potential and mean particle size where the change in pH of slurry will affected the conductivity, zeta potential and mean particle size of the slurry. The pH used in this study is 3.84, 5.26, 8.50 and 10.84 with amount of resin used is 5g, volume of spent slurry is 150 mL and time contact between resin and slurry is 120 minutes. As a conclusion, the removal of tungsten showed that the best removal in the acidic pH with 9.70% removal at pH 3.84 and the iron removal from slurry showed that the best removal is when the pH is alkali with 39.49% at pH 10.84.